1967
DOI: 10.1039/df9674300160
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin scattering of neutrons from liquids

Abstract: Inelastic coherent neutron scattering is called Brillouin scattering, if the momentum transferred to the scattering system is entirely taken up by collective particle motions. With this scattering, single excited states of such motions can be observed in polycrystals and in liquids in a similar way as in single crystals, provided the measurements are not too much contaminated by multiple scattering processes combining Bragg and inelastic scattering. Liquid and solid lead are investigated in this way. The compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

1969
1969
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
2
14
1
Order By: Relevance
“…A longitudinal mode, compatible with the higher frequency excitation previously reported by Dorner (Dorner et al, 1967) was reported, whose sound velocity is consistent with hydrodynamic value. The accessible kinematic range is too limited to asses any evidence of positive dispersion effect.…”
Section: Leadsupporting
confidence: 75%
See 4 more Smart Citations
“…A longitudinal mode, compatible with the higher frequency excitation previously reported by Dorner (Dorner et al, 1967) was reported, whose sound velocity is consistent with hydrodynamic value. The accessible kinematic range is too limited to asses any evidence of positive dispersion effect.…”
Section: Leadsupporting
confidence: 75%
“…Such processes, i.e. the presence of inelastic modes characterized by wavevectors which differ by multiples of the reciprocal lattice spacing, have been early reported by means of INS in liquid lead (Cocking and Egelstaff, 1965a;Dorner et al, 1965;Randolph and Singwi, 1966) and more recently in liquid lithium by means of IXS (Scopigno et al, 2001b). As correctly pointed out by Faber, the presence of these excitations does not imply the existence of genuine high Q modes, it rather indicates that umklapp processes may occur in liquid as much as in solid (Faber, 1972).…”
Section: B Dynamical Aspectsmentioning
confidence: 99%
See 3 more Smart Citations